Nonlinear Optics and Solid-State Lasers Advanced Concepts, Tuning-Fundamentals and Applications - Yao, Jianquan; Wang, Yuyue (Springer Series in Optical Sciences, 2012)
This book covers the complete spectrum of nonlinear optics and all solid state lasers.The book integrates theory, calculations and practical design, technology, experimental schemes and applications. With the expansion and further development of Laser technology, the wavelength spectrum of Lasers had to be enlarged, even to be tunable which requires the use of nonlinear optical and Laser tunable technology. It systematically summarizes and integrates the analysis of international achievements within the last 20 years in this field. It will be helpful for university teachers, graduate students as well as engineers.